Trophic interaction between striped marlin and swordfish using different timescales in waters around Baja California Sur, Mexico. Issue 1 (2nd January 2019) - Acosta-Pachón, Tatiana A.; Ortega-García, Sofía
ABSTRACT: Isotopic niche and resource partitioning were examined between striped marlin ( Kajikia audax ) and swordfish ( Xiphias gladius ) using stable isotope ratios from spine bone and muscle samples. The δ 13 C ( 13 C/ 12 C) and δ 15 N ( 15 N/ 14 N) values were measured in annual growth bands from fin spines and muscle collected from striped marlin and swordfish off Baja California Sur to evaluate the trophic interaction between these two species, the relative contribution of the main prey and the isotopic niche within two different timescales. Mean trophic level (TL) values were different when tissues were compared with the highest value found in muscle samples from K. audax . When TL was analysed in all growth bands for both species, no changes were detected throughout time, suggesting only minor differences in feeding habits between these species. We determined that Dosidicus gigas, Sthenoteuthis oualaniensis, and Ancistrocheirus lesueurii were the most important prey for both species, but the relative contribution of each of them to the diet differed. There is likely no trophic overlap between K. audax and X. gladius off Baja California Sur, as K. audax occupied a larger isotopic niche with more diverse prey than X. gladius .